Cancer neuroscience of brain metastasis: when in Rome, do as the Romans do - Karreman, Matthia A.; Winkler, Frank (Neuron, 2025)
It is becoming increasingly clear that the nervous system and cancer execute an intimate crosstalk, influencing cancer initiation, growth, spread, and resistance mechanisms. Cancer, vice versa, can change the nervous system. These mostly harmful neuro-cancer interactions constitute the emerging field of “cancer neuroscience.” Although this crosstalk is not limited to the central nervous system, the brain remains the site of particularly strong neural influences. In this review, we use the extensive knowledge of neuro-cancer interactions in primary brain tumors to highlight new discoveries about how neural influences govern metastatic tumor cells that originate from outside the brain and how, in turn, these cells can plastically modify the brain and its functions. Thus, we use brain metastasis, a particularly devastating complication of several common cancers, as a roadmap to conceptualize how far-reaching neuro-cancer interactions throughout the body can be and develop new ideas on how to use these insights for improved therapies.
Gesehen am 21.01.2026